2011
DOI: 10.1111/j.1532-849x.2011.00755.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chemical Disinfection and Accelerated Aging on Color Stability of Maxillofacial Silicone with Opacifiers

Abstract: Opacifier addition, chemical disinfection, and accelerated aging procedures affected the color stability of the maxillofacial silicone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
46
0
16

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 25 publications
3
46
0
16
Order By: Relevance
“…36,37 In general, the samples incorporating NPs showed significantly greater color stability compared with the control group ( Table 2). This finding is consistent with the results of other studies, 10,11,[38][39][40] which showed that addition of ZnO, TiO 2 , or BaSO 4 to polymeric materials can increase the longevity of maxillofacial prostheses by promoting maintenance of color. 10,12,[38][39][40] NPs are widely used, especially in sunscreen lotions, as inorganic absorbers of ultraviolet light.…”
supporting
confidence: 83%
See 4 more Smart Citations
“…36,37 In general, the samples incorporating NPs showed significantly greater color stability compared with the control group ( Table 2). This finding is consistent with the results of other studies, 10,11,[38][39][40] which showed that addition of ZnO, TiO 2 , or BaSO 4 to polymeric materials can increase the longevity of maxillofacial prostheses by promoting maintenance of color. 10,12,[38][39][40] NPs are widely used, especially in sunscreen lotions, as inorganic absorbers of ultraviolet light.…”
supporting
confidence: 83%
“…This finding is consistent with the results of other studies, 10,11,[38][39][40] which showed that addition of ZnO, TiO 2 , or BaSO 4 to polymeric materials can increase the longevity of maxillofacial prostheses by promoting maintenance of color. 10,12,[38][39][40] NPs are widely used, especially in sunscreen lotions, as inorganic absorbers of ultraviolet light. 22,38,41,42 Inorganic NPs differ from some organic ultraviolet absorbers, in that they do not migrate in the polymeric matrix.…”
supporting
confidence: 83%
See 3 more Smart Citations